BERBURU BABI SEBAGAI IDE PENCIPTAAN KARYA SENI GRAFIS DENGAN TEKNIK SERIGRAPHY - ANDRI PRATAMA, Dr. Budiwirman, M.Pd, Yofita Sandra, S.Pd., M.Pd (Serupa The Journal of Art Education, 2015)
Hunting is one of the people’s activities that have become part of peoplefor long time ago. In ancient time, hunting is as the livelihood, which one of the activity that still done until now about hunting is boar hunting. Boar hunting almost has for every place that lived in the rural areas that near from the forest area. The function and purpose boar hunting for Minangkabau’s people is to help the farmers for protecting their agricultural areas. The result of hunting is not for consumption, but just gived to their animals that is dogs.This project was done after several processes and more insipirated fromthe things that writer saw from boar hunting case. It is not only for wipe out the pets but also has other functions. The writer’s desire is this project can be enjoyable and understood by anyone. Furthermore, in making this project with the theme “Boar Hunting as The Idea of Creation Art Graphic Work with Serigraphy Technique” shows the shapes, concepts, steps and media with emphasized on the use of serigraphy technique.The project process was done by using a silk cloth or nylon called by monyl. The pores were left open so that the ink can pass and pores which are not covered by gelanthine/ulano/bremol which sweep the ink or paint by using rubber knife or rakelKata Kunci: Penciptaan Grafis Serigraphy